Skabies - Noviana Zara; Angie Delashynta Rianda (Jurnal Ilmu Kesehatan dan Gizi, 2023)
Patient An A was brought by her parents to the Children's polyclinic at the Lhoksukon Health Center with complaints of itching all over her body since the past 2 weeks. Complaints mainly in the area between the fingers, toes and in the groin area. The patient's mother said that her child complained of itching which felt worse at night. The patient's mother said that this complaint first appeared when her first child came home from the dayah during the school holidays. 3 weeks ago the patient brought his first child to the puskesmas with the same complaint before he returned to the dayah. And now the patient has just brought An A for treatment with the same complaint. From the examination results, HR: 87 x/I, RR: 18 x/I, temperature: 36.5 C. Primary data were obtained through alloanamnesa and physical examination by making home visits, filling out family folders, and filling out patient files. The assessment was carried out based on the initial holistic diagnosis, process and end of the visit both quantitatively and qualitatively. Interventions carried out include education about the causes of scabies to their families, education on environmental sanitation and hygiene and management of the disease and explaining complications that may arise from the patient's disease so that the patient's family maintains personal hygiene and environmental cleanliness.